Transtorno de estresse pós-traumático nos contextos de trabalho: das experiências traumáticas ao desenvolvimento do transtorno mental - Carlos Eduardo Carrusca Vieira (2014)
The present dissertation examines the etiology and development of trauma in work-related contexts, specially as regards Post-Traumatic Stress Disorder, a clinical condition which is becoming relatively frequent in contemporary times. On the basis of Georges Politzer's Concrete Psychology, we have striven to understand what is it that turns life situation into a traumatic experience, and how the passage is made between this situation and psychiatric condition. For that purpose, aside from a theoretical review by means of which studies concerning this illness were retrieved , three clinical case studies were undertaken regarding workers who lived potentially traumatic situations, the conclusions of which, in terms of the health/illness process, proved to be quite distinct. The first case involves a security guard who became afflicted with PTSD after the bank in which he worked was robbed. The second regards a warden who witnessed a suicide in the workplace, and consequently developed the same disorder, but was able to overcome it with the assistance of therapists and psychiatrists. The last concerns a bank teller who was kidnapped and kept in captivity but did not develop PTSD. These case studies were inspired by the biographical method propounded by Louis Le Guillant (2006), as well as by the theoretical frame of reference of the Clinic of Activity and Ergology. The conclusion is that psychological trauma consists in experiences which unsettle personal values and strongly affect individuals' self-esteem, PTSD emerging as a result of a synthesis of multiple traumatic experiences that strengthen one another. The feelings of impotence, abandonment, and insecurity as well as of depreciation which derive from the restriction of the power to act, from the absence of psychosocial support, from being judged and criticized by another over the course of potentially traumatic situations involving threats to the individual's and/or someone else's lives, all are characterized as major mediators in the development of PTSD.